The Sago Trade Dispute and Judicial Process in the Riau Lingga Kingdom: A Philological Analysis of Manuscript Letters from 1899-1900 - Rahmat, Syahrul; Fadilla, Zikra; Abd Rahim, Siti Azira (Journal of Philology and Historical Review, 2024)
This paper aims to explore the stemma method in philological studies and analyze the application of this method in researching ancient texts, especially in the aspect of manuscript genealogy. This paper arises in response to the challenges philologists often face when trying to determine the most appropriate method for their research into manuscripts. The presence of various methodological options can often confuse researchers and make them feel disoriented in their research. Therefore, this paper aims to provide guidance to readers in determining the appropriate steps in philological research, especially in the context of manuscripts that are considered ancient or old. One of the methods that will be discussed in detail is the use of Stemma, which is a very useful tool in uncovering the autograph authenticity of ancient manuscripts. By utilizing the Stemma method in research, researchers can take concrete steps to identify and analyze genealogical relationships between various ancient texts. This can help them achieve a deeper understanding of the origins and development of the texts, as well as identify the most authentic or authentic versions. Thus, through a better understanding of the theory, methodology and practical applications of philology, it is hoped that researchers will not feel confused or lost in their research, especially when they are dealing with texts that have a long and complex history.